3g+2(-7+3g)=1-g

Simple and best practice solution for 3g+2(-7+3g)=1-g equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3g+2(-7+3g)=1-g equation:


Simplifying
3g + 2(-7 + 3g) = 1 + -1g
3g + (-7 * 2 + 3g * 2) = 1 + -1g
3g + (-14 + 6g) = 1 + -1g

Reorder the terms:
-14 + 3g + 6g = 1 + -1g

Combine like terms: 3g + 6g = 9g
-14 + 9g = 1 + -1g

Solving
-14 + 9g = 1 + -1g

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add 'g' to each side of the equation.
-14 + 9g + g = 1 + -1g + g

Combine like terms: 9g + g = 10g
-14 + 10g = 1 + -1g + g

Combine like terms: -1g + g = 0
-14 + 10g = 1 + 0
-14 + 10g = 1

Add '14' to each side of the equation.
-14 + 14 + 10g = 1 + 14

Combine like terms: -14 + 14 = 0
0 + 10g = 1 + 14
10g = 1 + 14

Combine like terms: 1 + 14 = 15
10g = 15

Divide each side by '10'.
g = 1.5

Simplifying
g = 1.5

See similar equations:

| (3x+5y)-(4x+11)=0 | | 17y-5x=46 | | .14(14+3.5)-3q=9 | | -5=r-13 | | 2y+3=3(-2)-7 | | x-1(4x-7)=5x-(x+21) | | 3(x-9)=-39-x | | 7x+3=-7.5 | | (-A-5B+2)5AB= | | -4+6x=-34 | | 0.3(r+2)=-1.0(-2r-4) | | 6t^2+2t=2t(3t+1) | | 2y+3=3(0)-7 | | -7(p-8)= | | -2v-14=8(v+2) | | 4t=38+2t | | n-8=22+4 | | 3(4+4n)=18n+12-6n | | -5(x+7)= | | (2x+4)x=240 | | 6/15=3/x | | 2n^2=90 | | x(6)=60 | | n+3=17+4 | | 9h+11=5h-17 | | 2x(2x)= | | x(13)=52 | | 8x+9y=818 | | 400-313=x | | 6(b+4)=0 | | -9(6+u)=2u-10 | | 132=12(n+9) |

Equations solver categories